The Phenomenon of Slips of the Ear by English Education Department Students - Widayanti Widayanti (Universitas Pendidikan Indonesia (UPI), 2015)
The present study seeks to investigate the phenomenon of slips of the ear by English Education Department students. Data were taken from 10 students from different semester and have minimum 500 TOEFL score. Data were analyzed qualitatively supported by descriptive quantification and based on Bond’s (2005) slips of the ear theories. The findings show that the errors occur in lexical level and syntactical levels. The factors of the occurrences of slips of the ear can be because of the lack of lexical knowledge, the accent and dialect, the unfamiliarity with the words, or difficulties in segmenting utterances. The result of this study shows that the errors which occur most in all categories is in syntactical level, which is ill-formed utterances. Furthermore, this study supports the previous studies of slips of the ear proposed by Kusumarasdyati (2005) who states that when the listeners misperceive the utterances, they will add, omit, or substitute the utterances.Keywords: slips of the ear, music, lyrics, lexical, syntax